Elongated Photonic Nanojet from Truncated Cylindrical Zone Plate. (18th November 2012) - Stafeev, Sergey S.; Kotlyar, Victor V.
Abstract : Previously (Chen et al., 2004), it was shown that dielectric cylinder can form focal spots with small diameters and long depth. This type of focal spot was called photonic nanojet. In this paper, it was shown that dielectric cylinder of radius 595 nm (1.12 of wavelength) forms near the surface a photonic nanojet with diameter equal to 0.31 of wavelength and depth of focus equal to 0.57 of wavelength. Adding truncated concentric rings with radiuses equal to radiuses of zone plate to the cylinder increases the depth of focus to 1.18 of the wavelength. The diameter and intensity of focal spot near the cylinder surface remain unchanged.